Analisis Bibliometrik Penelitian Hadis Tarbawi pada Publikasi Scopus Tahun 2020–2025 - Nurlaila Turohmah; Abu Warasy Batula; Robiatul Adawiyah Ramadhani; Antiti Armilah; Yahya Rafi Sya’bani (Mustaneer : Journal of Islamic Thought and Civilization, 2026)
This study analyzes research trends in educational hadith (hadis tarbawi) within Scopus publications from 2020–2025 using a bibliometric approach. Its importance lies in mapping the development of prophetic pedagogy as a foundational value during the post-pandemic digital transformation of Islamic education. This research aims to map publication performance, identify key actors, and analyze thematic structures. Data were retrieved from the Scopus database using systematic selection and analyzed through performance analysis and science mapping via VOSviewer. The results reveal dynamic publication trends peaking in 2024 (179 documents), though academic collaboration remains fragmented across nine clusters. Geographically, Indonesia and Malaysia dominate the field, with six major thematic clusters reflecting multidimensionality. The novelty of this study is its contemporary temporal focus (2020–2025), highlighting a paradigm shift toward interdisciplinary and applied approaches. These findings provide strategic directions for strengthening educational hadith studies through enhanced international research collaboration and the integration of digital technology in contemporary Islamic pedagogy.